2016
DOI: 10.1016/j.jhin.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Hand soap contamination by Pseudomonas aeruginosa in a tertiary care hospital: no evidence of impact on patients

Abstract: Despite a highly contaminated soap, the combined investigation with DLST and WGS ruled out any impact on patients. Hand hygiene performed with alcohol-based solution for >15 years was probably the main reason. However, such contamination represents a putative reservoir of pathogens that should be avoided in the hospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
1
13
0
2
Order By: Relevance
“…In recent years, NGS coupled with WGS can be used for source tracking of P. aeruginosa in a hospital setting, and that acquisitions can be traced to a specific source within a hospital ward ( Quick et al, 2014 ). Besides, WGS could also be applied for epidemiological investigation of P. aeruginosa in intensive care units (ICU) ( Blanc et al, 2016 ). Recent years, NGS has been adapted for 16S rRNA gene based metagenomics study to rapidly catalog the bacterial species in mixed clinical specimens, without need for prior culture ( Lim et al, 2014 ).…”
Section: The New Era Of Molecular Diagnostics: Next Generation Sequenmentioning
confidence: 99%
“…In recent years, NGS coupled with WGS can be used for source tracking of P. aeruginosa in a hospital setting, and that acquisitions can be traced to a specific source within a hospital ward ( Quick et al, 2014 ). Besides, WGS could also be applied for epidemiological investigation of P. aeruginosa in intensive care units (ICU) ( Blanc et al, 2016 ). Recent years, NGS has been adapted for 16S rRNA gene based metagenomics study to rapidly catalog the bacterial species in mixed clinical specimens, without need for prior culture ( Lim et al, 2014 ).…”
Section: The New Era Of Molecular Diagnostics: Next Generation Sequenmentioning
confidence: 99%
“…Recent studies showed the added value of WGS for outbreak investigation retrospectively or prospectively compared to other typing techniques for P. aeruginosa [ 116 121 ] and A. baumannii [ 122 126 ]. Thrane et al made public a web tool ( https://cge.cbs.dtu.dk/services/PAst-1.0/ ) for in silico determination of the P. aeruginosa serotype, which can be useful to detect or characterise outbreak clones [ 120 ].…”
Section: Pseudomonas Aeruginosa and Acinetobacter mentioning
confidence: 99%
“…В настоящее время готовое жидкое мыло не подлежит обязательному лабораторному контролю при поступлении в медицинскую организацию, ни в дальнейшем при работе с ним. Однако возможность контаминации мыла микроорганизмами с последующим их распространением и развитием групповой заболеваемости возможна [18,19]. Вместе с тем, руки медицинского персонала в отделениях новорожденных и недоношенных детей -ведущий фактор передачи ИСМП, поскольку отличительной особенностью лечебно-диагностического процесса этих отделений является несоизмеримо большее, нежели в медицинских организациях иного профиля, количество контактов и площади контакта кожи пациентов с руками медицинского персонала.…”
Section: материалы и методыunclassified